Smouldering-Associated Worsening in Multiple Sclerosis : An International Consensus Statement on Definition, Biology, Clinical Implications, and Future Directions - Scalfari, Antonio; Traboulsee, Anthony; Oh, Jiwon; Airas, Laura; Bittner, Stefan; Calabrese, Massimiliano; Garcia Dominguez; Jose Manuel; Granziera, Cristina; Greenberg, Benjamin; Hellwig, Kerstin; Illes, Zsolt; et al. (John Wiley & Sons, 2026)
Despite therapeutic suppression of relapses, multiple sclerosis (MS) patients often experience subtle deterioration, which extends beyond the definition of "progression independent of relapsing activity." We propose the concept of smouldering-associated-worsening (SAW), encompassing physical and cognitive symptoms, resulting from smouldering pathological processes, which remain unmet therapeutic targets. We provide a consensus-based framework of possible pathological substrates and manifestations of smouldering MS, and we discuss clinical, radiological, and serum/cerebrospinal fluid biomarkers for potentially monitoring SAW. Finally, we share considerations for optimizing disease surveillance and implications for clinical trials to promote the integration of smouldering MS into routine practice and future research efforts. ANN NEUROL 2024.